A ocupação do espaço geográfico na micro região do Oiapoque - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1993)
This research is part of an interdisciplinary program called: History, Identity and Environment: Research on the Formation of a Multicultural Regional Complex in the Low-Oiapoque Region of Prehistory to this day. The program covers several areas of knowledge: Anthropology, Archaeology, Ethno-archaeology, Linguistics, Botany, Biogeography, Human Geography and Preservation of the Environment. The study area comprises the northern part of Amapá, specifically the Baixo-Oiapoque region. My subproject, "The Occupation of Geographic Space in the Micro Region of Oiapoque" aims to show the different forms of occupations and social manifestations that occurred in this area through various times. The bibliographic data show a great diversity of social relationships, which justifies further research. For the development of it, several stages of field are planned, where together with identification and subsequent excavations of archaeological sites, we will come into contact with the current populations. In this sense, obtaining more up-to-date data from these populations will allow a diagnosis of the cultural socioeconomic situation of the region.
The occupation of geographical space in the micro region of Oiapoque
Keywords: Oiapoque; Pré-História; Ocupação; CNPQ::CIENCIAS HUMANAS::ARQUEOLOGIA::ARQUEOLOGIA PRE-HISTORICA